2022
DOI: 10.1038/s41598-022-24560-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels and acute kidney injury: a systemic review and meta-analysis

Abstract: Numerous researches have evaluated the prevalence and clinical outcome of vitamin D deficiency in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD). But the quantitative vitamin D status in acute kidney injury (AKI) patients and its relationship with prognosis remains controversial. We conducted this systemic review and meta-analysis to assess the quantitative difference of vitamin D status, including serum 25(OH) D and 1,25(OH)2D levels, between AKI patients and non-AKI controls, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…69,70 Although a recent metaanalysis revealed that patients with AKI typically have lower calcitriol levels compared with healthy controls, another study reported significantly higher plasma calcitriol and P i in nonsurvivors compared with survivors in critically ill patients with AKI. 71,72 In our AKI model, the rise in calcitriol was driven by PTH as the increase in renal Cyp27b1 mRNA expression and the concomitant increase in calcitriol was fully abrogated in Pth 2/2 mice.…”
Section: Discussionmentioning
confidence: 86%
“…69,70 Although a recent metaanalysis revealed that patients with AKI typically have lower calcitriol levels compared with healthy controls, another study reported significantly higher plasma calcitriol and P i in nonsurvivors compared with survivors in critically ill patients with AKI. 71,72 In our AKI model, the rise in calcitriol was driven by PTH as the increase in renal Cyp27b1 mRNA expression and the concomitant increase in calcitriol was fully abrogated in Pth 2/2 mice.…”
Section: Discussionmentioning
confidence: 86%
“…Alterations of vitamin D metabolism contribute to elevation of PTH, inflammation, cardiovascular disease, and mineral bone disease in CKD, but its impact on AKI is less well established [28]. While observational studies have found consistent lower 1,25 (OH) 2 vitamin D and less consistent lower 25 (OH) vitamin D in patients with AKI versus without AKI in acute settings, the relationship between these measurements and relevant clinical outcomes such as AKI progression, need of dialysis or death has not been confirmed [26, 29]. While one should still acknowledge the possibility that certain patients with AKI or CKD could benefit from vitamin D supplementation, identification of more specific clinical sub-phenotypes and mechanisms of action is needed to assist in the design of future clinical trials.…”
Section: Endocrine-metabolic Changes In Akimentioning
confidence: 99%
“…Patients diagnosed with CKD have a progressive reduction of VitD levels ( LaClair et al, 2005 ; Nigwekar et al, 2012 ) and VitD deficiency is prevalent in 76.1% of stage 5 CKD patients submitted to the hemodialysis ( Del Valle et al, 2007 ; Cuppari and Garcia-Lopes, 2009 ; Zhang et al, 2022 ; Dhillon-Jhattu et al, 2023 ). Studies demonstrated in experimental models and in CKD patients a lower megalin expression in the kidneys ( Toi et al, 2019 ; Wen et al, 2022 ) and the absence of megalin in mice causes the inability of PTECs to capture the 25(OH)D3-VDBP complex, which in turn, are excreted in the urine, leading to a drastic reduction of plasma level of 25(OH)D3 and 1,25D3 ( Nykjaer et al, 1999 ; Negri, 2006 ).…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…CKD patients have a compromised VitD production that affects not only the kidney physiology, but also the systemic metabolism. Moreover, there is a diversity of studies that associate VitD deficiency and the development of pathological inflammation and renal fibrosis ( LaClair et al, 2005 ; Del Valle et al, 2007 ; Cuppari and Garcia-Lopes, 2009 ; Nigwekar et al, 2012 ; Wang et al, 2012 ; Zhang et al, 2022 ; Dhillon-Jhattu et al, 2023 ). Factors associated with the internalization of precursors for active VitD synthesis, such as endocytic receptors, are reduced in the injured kidneys, which could explain its low levels in CKD patients ( Toi et al, 2019 ; Wen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%